Flow Field Simulation and Measurement in Packed Beds Based on 4D‐X‐Ray Computed Tomography. Issue 5 (15th March 2023) - Martinez-Garcia, Jorge; Fenk, Benjamin; Gwerder, Damian; Schiffmann, David; Delgado-Diaz, William; Stamatiou, Anastasia; Fischer, Ludger J.; Schuetz, Philipp
Abstract: X‐ray computed tomography (XCT) combined with computational fluid dynamics (CFD) simulations have proved to be a powerful and versatile tool to describe fluids flow through packed bed systems. In this contribution, two examples of the application of XCT experiments to track the fluid flow and fluid penetration in packed bed systems are shown. The first one shows how geometrical information extracted from XCT measurements can be coupled to CFD simulations to assess fluid flows reliably. Here the example of a packed bed of three‐dimensional (3D) printed cylindrical‐shaped particles is considered. Finally, a short case study on the monitoring of the progress of the water penetration front in a packed bed composed of glass spheres using four‐dimensional (4D) XCT imaging data is presented. Abstract : This paper shows two examples of application of X‐ray computed tomography (XCT) to track the fluids flow through packed bed systems. Firstly, the combined used of XCT and CFD simulation is showcased to compute the fluid mean velocity and pressure drop fields in a packed bed of cylindrical particles. Then, the use of time‐lapse XCT imaging data to track the progression of water in a packed bed composed of spherical particles is presented.